Abdominal wall endometriosis: Literature review (Research, Society and Development, 2024)
Introduction: Endometriosis is a chronic, benign, estrogen-dependent and multifactorial gynecological disease that mainly affects women in the reproductive phase, but there are also cases described in pre-monarch and post-menopausal patients. Objective: This study seeks to compile the most recent information from the literature related to the etiology, pathophysiology, diagnosis, and treatment of endometriosis of the abdominal wall. Methodology: This is an integrated literature review, using the databases BVS, PubMed, SciELO, and Google Scholar, including articles published from 2019 to 2024, in Portuguese and English languages. Results: The focal mass of endometrial tissue present in the abdominal wall is the central element of the disease, causing abdominal pain associated with menstruation in patients. Furthermore, it remains a disease whose genesis has not been elucidated. The association of clinical evaluation and the use of images and/or blood markers helps to suspect the diagnosis, but only with histological analysis of the lesion can the diagnosis of APE be confirmed. To treat the disease, surgical excision is a definitive option, as is hormonal therapy. Conclusion: Endometriosis of the abdominal wall is a rare condition, the etiopathogenesis of which is still not well defined. Despite the scarcity of clinical studies, surgery is described as the sole, safe, and efficient therapeutic option.